Guerra tra giganti. Il riconoscimento del patrimonio archeologico sardo tra conservazione e accessibilità - Billeci, Bruno (Restauro Archeologico, 2023)
The recent initiatives aimed at promoting the recognition of the Sardinian archaeological heritage has generating two proposals included in the Tentative List: the "Domus de Janas", with surprising decorative elements, and the Nuragic civilization whose typological emblem, the nuraghe, is represented by the examples more significant. Both proposals concern the entire territory of Sardinia: here it is precisely archaeological architecture that constitutes the most recognizable asset with the most powerful meaning. Using the observation point of the Superintendency which participates in the process as territorial articulation of Ministry of Culture, it will be examine: • the legal status of the assets and the protection regime in place; • the conservation and maintenance projects made so far and for the future; • the state of accessibility to Heritage. The aims is to arrive at the drafting of a kind of state of the art and the guidelines for the recognition procedure.